Makna Diet Dalam Kampanye Body Positivity di Instagram @theantidietplan - Martha Claurena (Jurnal Ilmu Komunikasi, 2021)
Beauty is a benchmark, even though it is a relative concept in the culture of society, which will change over time. The most frequent and still popular beauty highlight among people is related to body shape. In the past, the ideal body image was depicted with a fat body, but now, through the onslaught of messages in the media, the ideal body is tall and thin. Various ways are done, especially by women to get the ideal body, one of which is through diet. Diet is considered to be one of the most effective and efficient ways to regulate eating patterns and life habits for a healthier and more stable body weight so as not to exceed normal body weight limits. There is a movement to campaign for body positivity, intended for women to accept whatever body shape they have and love them. This research focuses on observing the meaning of diet in campaigning for body positivity on the Instagram account @theantidietplan. This study uses a qualitative descriptive type approach using the critical discourse analysis method developed by Norman Fairclough. The results obtained from this study indicate that this account wants to explain the correct diet not because of the culture, but how to free oneself from these dietary cultures, then build a peaceful, trusting, and harmonious relationship with the food and body one has.